(untitled) (Linguostylistic Studies, 2019)
Genre typology of special dictionary reviews is a difficult task that implies detecting the specific features of every review genre to define its typological genre characteristics. The review of a terminology dictionary is 1) a kind of an expert opinion on the review of terminography edition, its estimation; 2) the representation of a critical sub-discourse, the basic genre of the terminography criticism. Analysis of the structure and the content of special dictionaries reviews, their multidimensional genre typology draws on the following characteristics (parameters): 1) the number of authors; 2) a type of the journal in which the review is published; 3) the amount of information in the review; 4) the number of dictionaries considered in the review; 5) the type of special dictionaries analyzed in the review; 6) the presence / absence of scientific discussion, i.e. the presence / absence of responses to the review; 7) the style of text presentation in the review; 8) the time to react to the dictionary publication. According to the characteristic ‘the number of authors’ there are the following types and subtypes of the reviews: 1) individual (according to the specialty of the experts – branch experts’ reviews and linguists’ / terminographers’ reviews); 2) collective (according to the specialty of the experts – the reviews of the representatives of the same specialty and the reviews of the representatives of different specialties). The selected types of the reviews by the specialization and the number of authors vary in volume, depth of the analysis, and argumentation accuracy regarding advantages or disadvantages of the dictionary. According to the characteristic ‘a type of the journal in which the review was published’ we distinguish (1) the reviews in scientific academic journals (by the type of a journal – linguistic and branch), (2) the reviews in non-academic (popular) journals (by the kind of media – electronic and paper). The existence of a large number of genre varieties and modern opportunities for review presentation attests a growing demand for the genre and its significance in improving the quality of national terminographic products.